2023
DOI: 10.3390/brainsci13030457
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids: Role in Neurodegenerative Diseases Remediation

Abstract: Numerous factors can contribute to the development of neurodegenerative disorders (NDs), such as Alzheimer’s disease, Parkinson’s disease, amyotrophic lateral sclerosis, Huntington’s disease, and multiple sclerosis. Oxidative stress (OS), a fairly common ND symptom, can be caused by more reactive oxygen species being made. In addition, the pathological state of NDs, which includes a high number of protein aggregates, could make chronic inflammation worse by activating microglia. Carotenoids, often known as “CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…36,[38][39][40] The possible protective effects of carotenoids in mental disorders and neurodegenerative diseases were also mentioned in other studies. 41,42 Higher serum concentrations and dietary intake doses of carotenoids were considered as protective lifestyle factors against chronic diseases. 27 A systemic meta-analysis based on various worldwide cohorts further indicated that a higher carotenoid intake might reduce the risk of all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36,[38][39][40] The possible protective effects of carotenoids in mental disorders and neurodegenerative diseases were also mentioned in other studies. 41,42 Higher serum concentrations and dietary intake doses of carotenoids were considered as protective lifestyle factors against chronic diseases. 27 A systemic meta-analysis based on various worldwide cohorts further indicated that a higher carotenoid intake might reduce the risk of all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…26,49 Singlet oxygen could lead to lipid peroxidation and ROS accumulation, whereas sustained high levels of ROS could cause oxidative stress and disrupt the redox balance. 41,42,50 As such, carotenoids are believed to have neuroprotective potential against oxidative stress-related neurodegenerative diseases, including Alzheimer's disease, Huntington's disease, and Parkinson's disease. 51,52 Also, sleep disorders are classified as oxidative stress-related diseases and are closely associated with mental disorders and neurodegenerative diseases.…”
Section: Food and Function Papermentioning
confidence: 99%
“…This protein leads to the formation of intracellular Lewy bodies. The aggregation of these proteins causes mitochondrial dysfunction, the generation of reactive oxygen species, microglial overactivation, and chronic inflammation, leading to DNA damage and apoptosis neurons in the brain [120,121].…”
Section: Antioxidant Activity Of Lycopene In Nervous System Disordersmentioning
confidence: 99%
“…1 The daily dietary intake of lutein is considered of important medical value as it combats a wide range of pathologies including diseases of the eyes, nervous system, heart, skin, and many others. [1][2][3] Moreover, an increased concentration of lutein in the blood is positively associated with a) increased respiratory function and b) decreased mortality from respiratory diseases. 4 A recent study highlights the urgency of implementing biopharmaceutical-nutrient rich dietary components, including lutein, in order to improve immune function and enhance antiviral activity against SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%